Pengaruh Corporate Governance, Kualitas Audit, dan Ukuran Perusahaan Terhadap Integritas Laporan Keuangan (Studi Pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar DI Bursa Efek Indonesia Tahun 2016-2020) - Khofifah Adinda Btr; Hendratno Hendratno (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine how the simultaneous and partial influence of corporate governance as proxied by managerial ownership, independent commissioners, audit committees, and audit quality and firm size on the integrity of financial statements. The population in this study are all food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The samples produced were 18 samples using purposive sampling technique. The data analysis used in this study is descriptive statistics and panel data regression using software eviews 12. The results of this study indicate that managerial ownership, independent commissioners, audit committees, audit quality and company size simultaneously affect the integrity of financial statements. Partially, the audit committee has a negative effect and firm size has a positive effect on the integrity of the financial statements. Meanwhile, managerial ownership, independent commissioners and audit quality have no effect on the integrity of the financial statements.